Comparison of medial and lateral tibial tunnel in pullout repair of posterior root tear of medial meniscus: Radiologic, clinical, and arthroscopic outcomes. (24th April 2020) - Kwon, Sai-Won; Kim, Jun Bum; Kim, Chang Hyun; Hong, Si John; Hong, Yong Cheol; Jang, Byung-Woong
Purpose: Medial meniscus posterior root tear (MMPRT) should be repaired to the correct position as possible to maintain hoop tension of the meniscus. In this study, we propose a comparison of the outcome between the medial tunnel and the lateral tunnel in the pullout suture technique using the tibial tunnel for anatomical repair of posterior root tear of medial meniscus. Methods: From April 2010, of patients who underwent pullout suture, 51 cases (24 medial tunnel group (MTG) and 27 lateral tunnel group (LTG)) were able to follow-up with second look arthroscopy. Original Coronal Ratio of Root Attachment (CRORA) was defined as the ratio of the distance from the medial edge of the tibial plateau to the root attach site divided by the entire tibial medial–lateral width on preoperative computed tomography. Error between postoperative CRORA and original CRORA was calculated. We compared this error, clinical outcome, and arthroscopic finding between MTG and LTG. Results: The mean error ratio of postoperative CRORA divided by original CRORA was 0.86 ± 0.11 in MTG, which was significantly ( p = 0.001) lower than that (1.02 ± 0.06) in LTG. The mean value of the root attach point in the MTG with a post/original CRORA value of 0.86 ± 0.11 means statistically significant medialization after the operation. There was no statistically significant difference in changes of International Knee Documentation Committee (IKDC) and Lysholom score between MTG and LTG. The difference between the two groups of arthritis progression was not statistically significant. Conclusion: In patients with MMPRT, CRORA may provide a basis for coronal assessment of root repair position before and after surgery, and lateral tibial tunnel technique can help anatomical repair by reducing technical error due to guide pin slip medially compared to medial tibial tunnel technique.